Prediction of local recurrence risk after neoadjuvant chemotherapy in patients with primary breast cancer: clinical utility of the MD Anderson Prognostic Index - Michel, Laura L.; Sommer, Laura; González Silos, Rosa; Lorenzo Bermejo, Justo; Au, Alexandra von; Seitz, Julia; Hennigs, André; Smetanay, Katharina; Golatta, Michael; Heil, Jörg; Schütz, Florian; Sohn, Christof; et al. (PLOS ONE, 2019)
Background Locoregional recurrence after neoadjuvant chemotherapy for primary breast cancer is associated with poor prognosis. It is essential to identify patients at high risk of locoregional recurrence who may benefit from extended local therapy. Here, we examined the prediction accuracy and clinical applicability of the MD Anderson Prognostic Index (MDAPI). Methods Prospective clinical data from 456 patients treated between 2003 and 2011 was analyzed. The Kaplan-Meier method was used to examine the probabilities of locoregional recurrence, local recurrence and distant metastases according to individual prognosis score, stratified by type of surgery (breast conserving therapy or mastectomy). The possible confounding of the relationship between recurrence risk and MDAPI by established risk factors was accounted for in multiple survival regression models. To define the clinical utility of the MDAPI we analyzed its performance to predict locoregional recurrence censoring patients with prior or simultaneous distant metastases. Results Mastectomized patients (42% of the patients) presented with more advanced tumor stage, lower tumor grade, hormone-receptor positive disease and consequently lower pathological complete response rates. Only a few patients presented with high-risk scores (2,7% MDAPI≥3). All patients with high-risk MDAPI score (MDAPI ≥3) who developed locoregional recurrence were simultaneously affected by distant metastases. Conclusion Our data do not support a clinical utility of the MDAPI to guide local therapy.